THE ROLE OF FAMILY CONSTELLATIONS ON DEVELOPMENT OF PROSOCIAL BEHAVIOUR AMONG THE REGULAR UNDERGRADUATE STUDENTS IN NAKURU COUNTY, KENYA - Runo, Billy Ben; Muola, James M.; Kay, James (kabarak university, 2022)
The study sought to assess the influence of Family constellations on psychosocial adjustments of regular third year undergraduate Students in Nakuru County, Kenya. The specific objective was to determine the influence of family constellations on prosocial behaviour development of regular undergraduate students in Nakuru County, Kenya. The study used a mixed-method research approach and adopted a cross-sectional survey research design. The target population was 2862 third year regular undergraduate students from five selected universities. A random sample of 307 students forming a 90.6 percent response rate participated in the study. Stratified random sampling was used to distribute the sample in the five selected universities. Primary data was collected using semi-structured questionnaire and interview schedule, while secondary data was collected from existing documents about the topic under study. Quantitative data was analyzed using descriptive statistics (frequencies, percentages and means) and inferential statistics (ANOVA and Chi Square tests) with the aid of Statistical Package for Social Sciences version 21.0 for Windows while qualitative data was analyzed using thematic content analysis. The study findings indicate that majority of the respondents came from dual (nuclear) parent families. There was no statistically significant difference in the pro-social behaviours development of regular undergraduate students from different family structures. The study recommends that there is a need for parents to maintain a unified family structure in order to encourage holistic psychosocial development and adjustment of their children in universities. There is a need for parents to create a warm close and supportive relationship with their children in universities. There is need to encourage university students to
Keywords: Family constellations; parenthood, psychosocial adjustment